2018
DOI: 10.1111/inm.12544
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of coping with multiple chronic conditions: A meta‐ethnography of qualitative work

Abstract: Multiple chronic conditions (MCCs) pose a major and growing burden on the individuals' health. The ways in which people cope with their stresses related to their chronic conditions are significant to their health outcomes. This review sought to understand lived experiences of coping with MCCs by a meta-ethnography of qualitative studies. Twenty-six studies were identified in four electronic databases including PubMed, PsycINFO, EMBASE, and CINAHL that were searched from 1966 to 2017. A seven-step analytic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 83 publications
1
23
0
Order By: Relevance
“…This study found that coping strategies adopted by people with MCCs interacted with chronic conditions management, psychological preservation and maintenance of social roles. Despite different labels in categorizing coping, the emerged strategies were congruent with past studies (Cheng et al, ; Löffler et al, ), which categorised coping strategies in the context of MCCs into three levels: practically, referring to the management of conditions; emotionally, referring to positive reframing; and socially, referring to the preservation of autonomy. In comparison, our participants displayed more particular skills, such as using TCM medications.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This study found that coping strategies adopted by people with MCCs interacted with chronic conditions management, psychological preservation and maintenance of social roles. Despite different labels in categorizing coping, the emerged strategies were congruent with past studies (Cheng et al, ; Löffler et al, ), which categorised coping strategies in the context of MCCs into three levels: practically, referring to the management of conditions; emotionally, referring to positive reframing; and socially, referring to the preservation of autonomy. In comparison, our participants displayed more particular skills, such as using TCM medications.…”
Section: Discussionsupporting
confidence: 79%
“…The clinical sheet obtained information regarding MCCs such as type and duration. Semi‐structured questions were developed by the first author based on findings from a past review (Cheng et al, ). An expert panel including two academic scholars and two clinical nurses helped to refine the interview questions by close reading (Castillo‐Montoya, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coping capacities [2] and stress resilience [24] are important factors in resisting major pandemic stress, as already shown for the H1N1 pandemic threat [25] , [26] . Coping capacities are important for managing illness in multiple chronic conditions such as diabetes, hypertension, depression [27] . They can be impaired in IBS, as we have previously shown with the French patients’ organization using a different QOL score which assessed coping capacities [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this practice, we have assessed the burden of treatment and identified areas such as health care services delivery and medical expenses as capable of overwhelming patients with T2DM. Although multimorbidity and trouble with medical expenses have been associated with higher treatment burden in all domains, 28,29 patients with financial resources and in seemingly good health (or able to control indicators, such as HbA 1c level) are also at risk of being overwhelmed by health care. This situation occurs because overwhelmed patients, to reconcile being unable to accomplish the recommended self-care work, may sacrifice safety or attempt to achieve health goals at the expense of other fulfilling activities.…”
Section: Discussionmentioning
confidence: 99%